EFIKASI DIRI DAN KESTABILAN EMOSI PADA PRESTASI BELAJAR - Sukatin; Indah Purnama Kharisma; Galuh Safitri (Department of Islamic Education Management, 2023)
Academic achievement is an important measure to evaluate an individual's success in acquiring knowledge and skills. In addition to academic factors, psychological aspects also influence the learning process. Self-efficacy, which is an individual's belief in their own abilities, and emotional stability are crucial factors in academic achievement. This study aims to investigate the relationship between self-efficacy and emotional stability and their impact on academic achievement. The research method used in this study is literature review. The results indicate that high self-efficacy contributes to better emotional stability, and good emotional stability can enhance individual self-efficacy. High self-efficacy and good emotional stability mutually support each other and enhance overall psychological well-being. Both factors also have a positive influence on academic achievement. Individuals with high self-efficacy and good emotional stability tend to have strong motivation, face challenges with optimism, and overcome learning obstacles. These findings have important implications for educational practitioners, policymakers, and researchers in the field of educational psychology to enhance the academic achievement of students and learners.